Implementasi Metode Ummi dalam Meningkatkan Kemampuan Membaca Al-Qur'an Peserta Didik di Taman Pendidikan Al-Qur'an Jannatul Firdaus Siman Ponorogo - Hafizh Raafi; Adnun Yelipele; Syarifah; Ihwan Mahmudi; Idam Musthofa (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The ability to read the Qur'an is a fundamental competency that every Muslim should possess. However, Qur'anic learning in many Taman Pendidikan Al-Qur'an (TPQ) still faces several challenges, including the use of non-standardized teaching methods, differences in students' initial reading abilities, and limited learning evaluation. One of the approaches developed to improve the quality of Qur'anic instruction is the Ummi Method, which applies a quality assurance system in teaching and learning. This study aimed to (1) describe the implementation of the Ummi Method at TPQ Jannatul Firdaus Siman Ponorogo, (2) analyze the supporting and inhibiting factors affecting its implementation, and (3) examine its contribution to improving students' Qur'an reading skills. This study employed a qualitative case study approach. Data were collected through observation, in-depth interviews with the head of the TPQ, a Qur'an teacher, a student, and a student's parent, as well as documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that the Ummi Method was implemented systematically through the stages of planning, implementation, and evaluation by applying three core strategies: Direct Method, Repetition, and Affection. Its successful implementation was supported by teacher competence, students' learning motivation, parental involvement, and a conducive learning environment, whereas differences in students' initial abilities, limited instructional time, and insufficient Qur'an reading practice at home became the main obstacles. Furthermore, the implementation of the Ummi Method contributed positively to improving students' pronunciation (makhārij al-ḥurūf), application of tajwīd rules, reading fluency, tartīl, and self-confidence in reading the Qur'an. This study concludes that the Ummi Method functions not merely as a Qur'an reading method but as an integrated quality assurance system that fosters sustainable Qur'anic literacy and supports the development of a Qur'anic generation in non-formal Islamic educational institutions